An Empirical Examination of Random Walk Hypothesis for Chittagong Stock Exchange - Mahmud, Md. Tapan; Ashif, Abu Sadat Muhammad (AIUB Journal of Business and Economics, 2015)
A capital market will play as a strong catalyst in the industrialization and economic development of the country.The Chittagong Stock Exchange (CSE) is a new and emerging stock exchange located in the port city of Chittagong in southeastern Bangladesh. This paper investigates whether the stock price index in the Chittagong Securities Market meets the criterion of weak-form market efficiency. This study seeks evidence supporting the existence of market efficiency in the Chittagong Stock Exchange Ltd (CSE).In this paper; we have analyzed the behavior of daily return of Chittagong Stock Market indices. The sample includes the daily price indices of all securities listed on the CSE All Share Index, CSE 30 index, and CSCX indices listed in the Chittagong stock market. The results from the unit root test, the ADF test on CSE All Share Index, CSE 30 index, and CSCX provide evidence that the Chittagong stock exchange (CSE) is not efficient even in weak form and CSE does not follow the random walk model.